2008
DOI: 10.1017/s0022215108001965
|View full text |Cite
|
Sign up to set email alerts
|

Superior semicircular canal dehiscence syndrome: a new aetiology

Abstract: We review superior semicircular canal dehiscence syndrome and its management, and we discuss common aetiologies, contrasting these with the unusual aetiology presented here. We conclude that superior semicircular canal dehiscence syndrome may present with a solely developmental aetiology, despite presenting late in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…This CT scan also shows a groove from the superior petrosal sinus on the temporal bone adjacent to the dehiscence. A recent case report has suggested that such developmental abnormalities may account for some cases of the Tullio phenomenon [33].…”
Section: Ocular Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This CT scan also shows a groove from the superior petrosal sinus on the temporal bone adjacent to the dehiscence. A recent case report has suggested that such developmental abnormalities may account for some cases of the Tullio phenomenon [33].…”
Section: Ocular Movementsmentioning
confidence: 99%
“…Although this may be regarded a normal anatomical variant, it has been suggested that such developmental abnormalities may underlie some cases of Tullio phenomenon (see Ref. [33])…”
Section: Ocular Movementsmentioning
confidence: 99%
“…When the SCC is too close to the developing dura, cartilage formation covering the superior part of the SSC may be disturbed, leading to a bone defect on the roof of the SSC. An enlarged superior petrosal sinus was also reported to be a cause of SCD and this was also explained in the same manner [17].…”
Section: Discussionmentioning
confidence: 78%
“…Involvement of the petrosal sinus with SCD has been documented in a number of case reports [25,26] and several case series [2,13,19]. They report SPS involvement in 9-32%.…”
Section: Discussionmentioning
confidence: 99%